Evidências científicas para a prevenção da violência de gênero contra meninas adolescentes e jovens mulheres - Bachega, Denise (Universidade Federal de São Carlos, 2020)
Gender-based violence (GBV) is a global public health problem that affects women of all nationalities, ages, social classes, cultural, ethnic and racial groups and at all educational levels. Studies have demonstrated the importance of socialization for the attraction towards violence as the root of this phenomenon, with emphasis on the socialization that occurs in the school context. Based on investigations carried out in the research group in which this thesis was developed, NIASE, the present research had as main focus to identify actions aimed at girls and young women that prevent GBV, seeking to overcome it. For this purpose, a bibliographic research of scientific papers was carried out in the databases Scielo, Google Scholar, ERIC and Web of Science, using descriptors such as “gender violence”, in Portuguese and in English. A general characterization of the papers was carried out regarding: year and type of publication, country, area of knowledge and type of work presented in relation to the GBV (interventional, descriptive, theoretical or literature review). The results presented in the Brazilian production are more focused on the descriptive aspects in relation to the VdG than the intervening ones and only one intervention carried out from the Education area was found. In the international literature, however, most of the papers that carried out intervention were in the Educational area. No Brazilian papers, or references to the national context, were found in the consulted international databases. In addition, the results found were also analyzed and discussed in relation to the transformative dimension, that is, aspects of reality that address ways of overcoming a VdG; and to the exclusionary dimension, that is, aspects of reality discussed in the paper that reinforce socialization for the attraction towards violence, promote gender violence or tolerance to it. It is highlighted that national papers have a greater number of exclusonary elements than papers analyzed in the international literature. The analysis of the papers indicates the challenges still faced in the country, since there is a scarcity of knowledge production that presents concrete answers to this problem, which is still so present in our society and which hinders the transformation of the violent social context in which we live. At the end, indications on the relevant aspects to be considered when carrying out VdG preventives are displayed.
Scientific evidence for the prevention of gender-based violence against adolescent girls and young women
Keywords: Violência de gênero; Violência contra mulher; Adolescentes; Escola; Prevenção; Gender-based violence; Violence against women; Adolescents; School; Prevention; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO